Rick Turner and South Africa's "Sixties". Issue 4 (1st December 2016) - Lichtenstein, Alex
Abstract : This article examines the life and thought of South African radical philosopher Richard" Rick" Turner (1941–1978), a crucial figure in the 1973 anti‐apartheid political conjuncture known as the" Durban Moment." Though steeped in existentialist philosophy, Turner's real contribution to New Left thought in South Africa came elsewhere. Turner's receptivity to" Black Consciousness, " his vision of radical pedagogy, and his commitment to participatory democracy and" workers' control" all made a deep imprint on Black working class mobilization and the birth of a democratic trade union movement in South Africa.